Nutritional benefits of improved post-harvest handling practices for maize and common beans in Northern Tanzania: a quantitative farm-level assessment - Mutungi, C.; Tungu, J.; Amri, A.; Gaspar, A.; Abass, A. (Elsevier, 2022)
The efficacy of improved post-harvest practices for reducing food losses is often reported, but the nutritional benefits remain much less expounded. Meanwhile, nutrient concentration changes during the post-harvest period can influence potential nutrition gains targeted to benefit households. We analyzed contents of selected nutrients in farmers’ maize and common bean stocks under ordinary and improved practices at different post-harvest stages and related them to the physical quality. The improved practices comprised drying on tarpaulins, improved threshing, cleaning, and air-tight storage. By calibrating the actual nutrient contents against losses data, we estimated nutrient abundance levels and applied household farm production and nutrient demand data to estimate potential nutritional gains. Post-harvest stage (S), practice (P), and the S*P interaction significantly influenced physical quality, actual nutrient contents, and nutrient abundance. The actual contents of most nutrients increased or decreased monotonically with grain damage. For maize, improved practices begot more calories (4.7%), protein (13.9%), and minerals (4–26%) at the mid stage of the post-harvest season and even more calories (40%), protein (34%), and minerals (2–105%) at the late stage. The gains were lower for beans–calories 6.5%, protein 8.7%, minerals 1–55%. Dry matter loss and nutrient enrichment effects were responsible for variable nutrient concentrations in the maize and beans. The dry matter loss effect mainly influenced macronutrient abundance levels, especially in maize, whereas the enrichment effect mainly influenced minerals abundance with stronger influence on the beans than maize. Nutrients redeemed by improved practices at the late stage corresponded to 16–55 more days of calories and protein sufficiency for households, and significant extra days of minerals sufficiency, including Zn (16–56), Cu (23–81), Mg (45–166), and K (7–26). The gains have relevance for nutritionally-challenged households.